2012
DOI: 10.5811/westjem.2011.9.6669
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician Estimation of Blood Loss

Abstract: IntroductionEmergency physicians (EP) frequently estimate blood loss, which can have implications for clinical care. The objectives of this study were to examine EP accuracy in estimating blood loss on different surfaces and compare attending physician and resident performance.MethodsA sample of 56 emergency department (ED) physicians (30 attending physicians and 26 residents) were asked to estimate the amount of moulage blood present in 4 scenarios: 500 mL spilled onto an ED cot; 25 mL spilled onto a 10-pack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
1
14
1
1
Order By: Relevance
“…Our results indicated no difference between the role groups. This is contrary to Ashburn et al (38) who found that attending physician had a reduced error compared with residents. Our finding is, however, similar to Adkins et al (5) who investigated groups of anesthesia providers and found no difference between different roles and levels of experience and expertise.…”
Section: Pre-guide Accuracycontrasting
confidence: 77%
“…Our results indicated no difference between the role groups. This is contrary to Ashburn et al (38) who found that attending physician had a reduced error compared with residents. Our finding is, however, similar to Adkins et al (5) who investigated groups of anesthesia providers and found no difference between different roles and levels of experience and expertise.…”
Section: Pre-guide Accuracycontrasting
confidence: 77%
“…The visualization method requires suppositions dependent on blood loss found in suction canisters, surgical sponges, surgical drapes/surgical gowns, and the operating room environment (ie, operating room floor). 18 This method has been found to be inaccurate for estimating blood loss in many studies 11 , 19 20 21 22 23 24 25 that show that physicians underestimate blood loss in high blood loss situations and overestimate in low blood loss situations. 9 , 11 , 18…”
Section: Discussion and Summarymentioning
confidence: 99%
“…As estimated blood loss is an inherently unreliable and often underestimated , CB was defined as any patient identified by a definition of MT. Reports of all RBC units issued (including date and time) and transfused in calendar year 2010 were obtained from hospital blood banks.…”
Section: Methodsmentioning
confidence: 99%